2012
DOI: 10.1073/pnas.1111715109
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of value representation by social context in the primate orbitofrontal cortex

Abstract: The authors note that on page 2126, left column, lines 6-10 of the abstract, "Behaviorally, monkeys discriminated between cues signaling small and large rewards, and between cues signaling rewards to self only and reward to both self and another monkey, with a preference for the former over the latter in both instances," should instead appear as "Behaviorally, monkeys discriminated between cues signaling large and small rewards, and between cues signaling rewards to self only and reward to both self and anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 40 publications
11
113
0
Order By: Relevance
“…Eye fixation patterns revealed that the recorded animal closely observed the conspecific's reward-predicting stimuli, face and spout ( Fig. 1 E and F), confirming previous observations during social interaction of nonhuman primates (3,8,19). Without being required, the passive, nonacting animal maintained its hand on the resting key (Fig.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Eye fixation patterns revealed that the recorded animal closely observed the conspecific's reward-predicting stimuli, face and spout ( Fig. 1 E and F), confirming previous observations during social interaction of nonhuman primates (3,8,19). Without being required, the passive, nonacting animal maintained its hand on the resting key (Fig.…”
Section: Resultssupporting
confidence: 75%
“…The principal hypothesis is stated in the unrestricted model Y = β 0 + β 1 A + β 2 W + β 3 Z + β 4 AW + β 5 AZ + e; [1] where Y is neuronal activity, A is actor (recorded animal acts = 1, conspecific acts = 0), W is reward for recorded animal (reward = 1, no reward = 0), and Z is reward for conspecific animal (reward = 1, no reward = 0). The two models of most interest were Y = β 0 + β 1 A + β 2 W + β 4 AW + e; [2] which tests neuronal coding of actor for own reward, and Y = β 0 + β 1 A + β 3 Z + β 5 AZ + e; [3] which tests neuronal coding of actor for conspecific's reward. We also included a model that tests coding of reward only Y = β 0 + β 2 W + β 3 Z + e: [4] All models implied by the unrestricted model (Eq.…”
Section: Eye Movement Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The observed correlations between target popularity and activity in valuation and social cognition regions confirmed our primary hypotheses, which led to our second question: Do the two systems track popularity in parallel (independently) or serially, with one system assuming a primary role that mediates the popularity-activity relationship for the other? We predicted the valuation system would function as mediator based on the aforementioned literatures in social psychology [i.e., it is highstatus individuals' social importance that motivates others to predict their mental states (25)(26)(27)(28)] and nonhuman primate neurophysiology [i.e., neurons in valuation regions encode social value and signal presence of high-status group members (19)(20)(21)(22)]. To test this prediction, we performed multilevel mediation analyses, assessing whether valuation system activity explains the observed relationship between target popularity and social cognition system activity.…”
Section: And Person Judgment Tasks (See Ref 23 For Review)mentioning
confidence: 99%
“…These densely interconnected regions (13), henceforth referred to collectively as the "valuation system," are consistently implicated in processing the affective value and motivational significance of various stimuli, including other people (13)(14)(15)(16)(17)(18). Although human neuroscience research has yet to investigate sociometric popularity, nonhuman primate researchers have found that neurons in these regions signal group members' dominance rank (19)(20)(21) and proposed that the vmPFC, VS, and amygdala interact to encode, monitor, and signal other individuals' social value (22). If tracking group members' popularity depends on the motivational significance…”
mentioning
confidence: 99%